2012
DOI: 10.3390/md10040762
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Tailoring for the Production of Anti-Infective Cytosporones from the Marine Fungus Leucostoma persoonii

Abstract: Recent genomic studies have demonstrated that fungi can possess gene clusters encoding for the production of previously unobserved secondary metabolites. Activation of these attenuated or silenced genes to obtain either improved titers of known compounds or new ones altogether has been a subject of considerable interest. In our efforts to discover new chemotypes that are effective against infectious diseases, including malaria and methicillin-resistant Staphylococcus aureus (MRSA), we have isolated a strain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 26 publications
(27 reference statements)
1
61
0
2
Order By: Relevance
“…These marine fungi are an important source of structurally unique and biologically active natural products. Recent studies revealed that the cryptic biosynthetic pathways of fungi can be activated and the chemical diversity of their metabolites can be maximized by alternating their cultivation parameters systematically, such as the components of the media [1,2], co-culture [3,4], feeding precursors [5,6] and the addition of enzyme inhibitors [7,8]. For example, marine fungus Chondrostereum sp., which was isolated from soft coral Sarcophyton tortuosum , grows in different culture media and can produce various novel bioactive hirsutane-type sesquiterpenoids [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These marine fungi are an important source of structurally unique and biologically active natural products. Recent studies revealed that the cryptic biosynthetic pathways of fungi can be activated and the chemical diversity of their metabolites can be maximized by alternating their cultivation parameters systematically, such as the components of the media [1,2], co-culture [3,4], feeding precursors [5,6] and the addition of enzyme inhibitors [7,8]. For example, marine fungus Chondrostereum sp., which was isolated from soft coral Sarcophyton tortuosum , grows in different culture media and can produce various novel bioactive hirsutane-type sesquiterpenoids [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports [10,15], all epigenetic modifiers were tested at 100 µM as the standard concentration in the study. After 14 days of fermentation, ensuring the generation of enough biomass in the control conditions, submerged culture differences in morphology and SMs profiles were analyzed visually and by UHPLC-UV at 210 nm.…”
Section: Screening Of Epigenetic Modifiers Effects On Fungal Endophytesmentioning
confidence: 99%
“…The majority of these epigenetic studies report the effect of using hydroxamic-acid compounds, such as SAHA (8), with similar HDAC inhibitory effects; e.g.,: the production of a new fungal biosynthetic cyclodepsipeptide (EMG-556) by Microascus sp. when cultured with SAHA [9], the production of new anti-infective cytosporones by the marine fungus Leucostoma persoonii [10] or, the biosynthesis of novel fusaric acid derivatives by the Datura stramonium endophyte when SBHA was added to its production medium [11].…”
Section: Introductionmentioning
confidence: 99%
“…• 5-Butyl-6-oxo-1,6-dihydropyridine-2-carboxylic acid • 5-(But-9-enyl)-6-oxo-1,6-dihydropyridine-2-carboxylic acid Chen et al (2013) Sodium butyrate (HDAC inhibitor) Leucostoma persoonii • Novel compound -cytosporone R • Enhanced production of known cytosporones B (360%), C (580%) and E (890%) Beau et al (2012) 5-Azacytidine (DNMT inhibitor) and/or suberoylanilide hydroxamic acid (HDAC inhibitor)…”
Section: Resultsmentioning
confidence: 99%